Case Study On Sentral College Penang The Marketing Strategy To Capture Market Share - Tan, Peng Hooi (2014)
This case study was developed based on a private higher education institution (PI-IE!) located in Penang which offer tertiary education programs ranges from Certificate, Diploma, Degree, Skill-based training as well as Professional qualifications. In this case study explores what are the issues faces a small medium PHEI which IS operating in a higher competitive industry, competing with 559 PHEI including public higher education institution. I analyze the issues face by the industry as well as specific issues faced by the company. From the analysis through interviewing with the management and observing the activity in the company, I can identify three root causes of the problem facing the company. First being the lack of corporate governance which results in Management unable to act confidently. Second being the lack of information for the management to be able to make decision efficiently and thirdly being the marketing function not fully utilizes all the appropriate tools to attract the right customers. From the root causes a few short-term and long term solutions are suggested.